Blood Collection in Strong Acidic Citrate Anticoagulant Used in a Study of Dietary Influence on Basal tPA Activity - Rånby, Mats; Sundell, I Birgitta; Nilsson, Torbjörn K (Thrombosis and Haemostasis, 1989)
Tissue plasminogen activator (tPA) activity in blood and blood plasma has been difficult to determine because it is unstable, especially in subjects with high levels of plasminogen activator inhibitor type 1 (PAI-1). We have attempted to stabilize the tPA activity by collecting 9 volumes of blood in 1 volume acidic citrate buffer which immediately lowers the pH of the blood. At final blood pH of 4.9 to 6.3, consistent and high tPA activity levels were found. One acidic citrate buffer composition, 0.5 mol/1 citrate buffer pH 4.0, resulted in final blood pH 5.5, tPA half-life of 10 days and an acceptably low degree of haemolysis. This anticoagulant composition was selected for more extensive evaluation and was used to collect blood plasma samples from 29 volunteers in the morning after a 10-minute bed rest. Basal tPA activity, mean and SD, was 0.47 ±0.21 IU/ml. After donating of the first blood sample, 10 of the volunteers entered into a 24-hour fast after which they donated a second sample. During the fast, the basal tPA activity increased from 0.34 ±0.21 to 0.47 ±0.23 IU/ml (p = 0.05) and the PAI-1 activity decreased from 11.4±11.6 to 6.3±8.9 U/ml (p = 0.04).
Keywords: Tissue plasminogen activator; tPA; tPA activity; Basal tPA activity; Blood sample collection; Citrate buffer; Diet experiment